Positive electrode active material precusor and manufacturing method of positive electrode active material precusor

The CSTR process with controlled nitrogen flow and pH conditions addresses the challenge of producing small, uniform, and highly spherical cathode active material precursors, enhancing calcination efficiency and enabling single-particle cathode active material manufacturing.

KR103043940B1Active Publication Date: 2026-11-05LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020220019032
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-14
Publication Date
2026-11-05
Estimated Expiration
2042-02-14

AI Technical Summary

Technical Problem

Existing methods for manufacturing cathode active material precursors face challenges in achieving small, uniform particle size and high sphericity, particularly when using batch reactors, while continuous stirred tank reactors result in simultaneous nucleation and growth issues.

Method used

A method involving a continuous stirred tank reactor (CSTR) process where a transition metal-containing solution, ammonium cation complex-forming agent, and basic aqueous solution are introduced to generate nuclei, with controlled nitrogen flow and pH conditions to produce positive electrode active material precursors with specific molar ratios, enabling small and uniform particle sizes and high sphericity.

Benefits of technology

The method achieves positive electrode active material precursors with an average particle size of approximately 1 μm, uniform particle size, and high sphericity, facilitating even heat transfer during calcination and enabling the production of single-particle cathode active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112022016386350-PAT00002_ABST
    Figure 112022016386350-PAT00002_ABST
Patent Text Reader

Abstract

The present invention comprises the step of (A) continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution into a continuous stirred tank reactor (CSTR) to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; The invention relates to a method for manufacturing a positive active material precursor and a positive active material precursor manufactured therefrom, comprising: (B) a step of, when the reactor is full, opening an overflow pipe to obtain the positive active material precursor manufactured in step (A), and simultaneously flowing nitrogen gas into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute, and continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; wherein, in steps (A) and (B), the ammonium cation complex-forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex-forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor is 0.1 to 0.4.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a positive electrode active material precursor and a method for manufacturing a positive electrode active material precursor. Background Technology

[0003] With the increasing technological development and demand for mobile devices and electric vehicles, the demand for secondary batteries as an energy source is rapidly rising. Among secondary batteries, lithium-ion batteries, which possess high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Lithium composite transition metal oxides are used as cathode active materials for lithium secondary batteries, and with the recent expansion of demand for automotive batteries requiring long-distance driving capabilities, the development of lithium nickel-cobalt-manganese metal oxides with high nickel content is actively underway to secure high capacity.

[0005] Meanwhile, while increasing the nickel content is advantageous for securing high capacity, it leads to problems such as reduced structural, chemical, and thermal stability. To address this, the development of single-particle cathode active materials is underway. To successfully manufacture single-particle cathode active materials, heat must be transferred evenly and effectively during the calcination process of the cathode active material precursor; for this even and effective heat transfer, the particle size of the cathode active material precursor must be small and uniform, and the sphericity must be high.

[0006] Conventionally, batch reactors were used to manufacture cathode active material precursors with uniform particle size and high sphericity. However, when using batch reactors, there is a problem in that the cathode active material precursor continues to grow within the reactor, making it difficult to form precursors with small particle sizes.

[0007] Meanwhile, when manufacturing a cathode active material precursor using a continuous stirred tank reactor according to previously disclosed methods, although it is possible to form a precursor with small particle size, there is a problem in that it is difficult to manufacture a cathode active material precursor with uniform particle size and high sphericity because nucleation growth and nucleation occur simultaneously.

[0008] Therefore, there is a need to develop a method for manufacturing cathode active material precursors that are small in particle size, uniform, and highly spherical. The problem to be solved

[0010] The present invention is intended to solve the above-mentioned problems, and the average particle size (D 50 The present invention aims to provide a positive electrode active material precursor having a particle size of approximately 1 μm, uniform particle size, and high sphericity, and a method for manufacturing the positive electrode active material precursor. means of solving the problem

[0012] The present invention provides a method for manufacturing a positive electrode active material precursor and a positive electrode active material precursor.

[0014] (1) The present invention comprises the step of (A) continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution into a continuous stirred tank reactor (CSTR) to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; and (B) when the reactor is full, open the overflow pipe to obtain the positive active material precursor prepared in step (A), and simultaneously flow nitrogen gas into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute, while continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; wherein in steps (A) and (B), the ammonium cation complex-forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex-forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor is 0.1 to 0.4.

[0015] (2) The present invention provides a method for manufacturing a positive electrode active material precursor according to (1), wherein the transition metal-containing solution contains 70 mol% or more of nickel relative to the total molar amount of the transition metal.

[0016] (3) The present invention provides a method for manufacturing a positive active material precursor, wherein step (A) of (1) or (2) is performed under an inert atmosphere.

[0017] (4) The present invention provides a method for manufacturing a positive electrode active material precursor, wherein in any one of (1) to (3), step (A) is performed by flowing nitrogen gas into the reactor at a flow rate of 5 volume% or more and less than 20 volume% of the total volume of the reactor per minute.

[0018] (5) The present invention provides a method for manufacturing a positive electrode active material precursor, wherein in any one of (1) to (4), step (A) and step (B) are performed under a pH of 12.0 to 13.0.

[0019] (6) The present invention provides a method for manufacturing a positive electrode active material precursor, wherein in any one of (1) to (5), the nucleation of the precursor particles in steps (A) and (B) occurs at a pH lower than the nucleation of the precursor particles.

[0020] (7) The present invention has an average particle size (D 50 The present invention provides a positive electrode active material precursor having a thickness of 0.95㎛ to 1.5㎛, a span value of 1.5 or less according to Formula 1 below, and a sphericity of 1 to 1.3.

[0021] [Equation 1]

[0022] Span = (D 95 -D5) / D 50

[0023] (8) The present invention provides a positive active material precursor according to (7), wherein the positive active material precursor has a composition represented by the following chemical formula 1 or chemical formula 2.

[0024] [Chemical Formula 1]

[0025] Ni a1 Co b1 M1 c1 M2 d1 (OH)2

[0026] In the above chemical formula 1, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a1<1.0, 0 <b1<0.3, 0<c1<0.3, 0≤d1≤0.02이며,

[0027] [Chemical Formula 2]

[0028] Ni a2 Co b2 M1 c2 M2 d2 O·OH

[0029] In the above chemical formula 2, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a2<1.0, 0 <b2<0.3, 0<c2<0.3, 0≤d2≤0.02이다.

[0030] (9) The present invention provides a positive active material precursor having a tap density of 1.3 g / ml or more and 1.5 g / ml or less in accordance with (7) or (8).

[0031] (10) The present invention provides a positive active material that is a calcined product of a mixture of a positive active material precursor of any one of (7) to (9) and a lithium raw material.

[0032] (11) The present invention provides a positive active material in the form of a single particle, wherein the positive active material is the positive active material of (10). Effects of the invention

[0034] According to the method for manufacturing a positive electrode active material precursor of the present invention, the average particle size (D 50 It is possible to provide a positive electrode active material precursor that is small (approximately 1㎛), has a uniform particle size, and has high sphericity. In addition, since the method for manufacturing the positive electrode active material precursor of the present invention utilizes a CSTR reactor, there is no limit to the production volume.

[0035] The positive active material precursor according to the present invention has an average particle size (D 50The particle size is small, approximately 1㎛, and has a uniform particle size and high sphericity, so the precursor can receive heat uniformly when mixed with lithium raw material and calcined. Accordingly, a single-particle cathode active material can be easily manufactured. Brief explanation of the drawing

[0037] FIG. 1 is a graph showing the particle size distribution of the cathode active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5. Figure 2 is an SEM image showing the positive electrode active material precursor prepared in Example 1. Figure 3 is an SEM image showing the positive active material precursor prepared in Example 2. Figure 4 is an SEM image showing the positive electrode active material precursor prepared in Example 3. Figure 5 is an SEM image showing the cathode active material precursor prepared in Comparative Example 1. Figure 6 is an SEM image showing the positive active material precursor prepared in Comparative Example 2. Figure 7 is an SEM image showing the positive active material precursor prepared in Comparative Example 3. Figure 8 is an SEM image showing the cathode active material precursor prepared in Comparative Example 4. Figure 9 is an SEM image showing the positive active material precursor prepared in Comparative Example 5. Figure 10 is an SEM image of a positive electrode active material prepared using the positive electrode active material precursor of Example 1. Figure 11 is an SEM image of a positive electrode active material prepared using the positive electrode active material precursor of Comparative Example 1. Specific details for implementing the invention

[0038] Hereinafter, the present invention will be described in more detail to aid in understanding the invention.

[0039] Terms and words used in the description and claims of the present invention should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0041] In this specification, D5, D 50 and D 95 Each can be defined as the particle size corresponding to 5%, 50%, and 95% of the cumulative volume on the particle size distribution curve (graph curve of the particle size distribution). The above D5, D 50 and D 95 This can be measured, for example, using a laser diffraction method. The laser diffraction method generally enables the measurement of particle sizes ranging from a few nanometers to several millimeters, and allows for the acquisition of results with high reproducibility and high resolution. In this specification, the average particle size is the above D 50 It means.

[0042] In this specification, 'single-particle type positive active material' refers to a positive active material composed of 10 or fewer primary particles, as opposed to a spherical secondary particle type positive active material formed by the aggregation of tens to hundreds of primary particles manufactured by conventional methods. Specifically, in the present invention, the single-particle type positive active material may be a single particle composed of one primary particle, or a secondary particle type formed by the aggregation of several primary particles. In this case, 'primary particle' refers to the smallest unit of a particle recognized when the positive active material is observed through a scanning electron microscope.

[0043] In this specification, sphericity is a value obtained by shape analysis of scanning electron microscope images, and can be defined as the aspect ratio, which is the ratio of the major axis length to the minor axis length in the cross-section of a positive electrode active material precursor particle. Specifically, the dispersion of the particle's outer point (λ1 2 The direction in which ) is largest is called the major axis, and the dispersion of the particle's outer points (λ2 2 When the direction with the smallest aspect is called the short axis, the aspect ratio is λ1 / λ2.

[0044] In this specification, tap density is the apparent density of particles obtained by filling 50g of a positive active material precursor into a 100ml container and then vibrating it under certain conditions (3000 tappings), and can be measured using a tap density tester (KYT-4000, Seishin Co.).

[0045] In this specification, pH is a value measured at 25°C.

[0047] Method for manufacturing a positive electrode active material precursor

[0048] First, a method for manufacturing a positive electrode active material precursor according to the present invention will be described.

[0050] A method for manufacturing a positive electrode active material precursor according to the present invention comprises: (A) a step of continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution into a continuous stirred tank reactor (CSTR) to generate and grow nuclei of positive electrode active material precursor particles through a precipitation reaction; and (B) a step of, when the reactor is full, opening an overflow pipe to obtain the positive electrode active material precursor produced in step (A), and simultaneously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute to generate and grow nuclei of positive electrode active material precursor particles through a precipitation reaction. At this time, in steps (A) and (B) above, the ammonium cation complex forming agent is introduced such that the molar ratio of ammonia included in the ammonium cation complex forming agent to the total molar amount of transition metal included in the transition metal-containing solution introduced into the reactor is 0.1 to 0.4.

[0051] In step (B) above, if nitrogen gas is flowed into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute, the inflow of external air through the overflow pipe can be blocked, thereby preventing excessive nucleation due to the oxidizing atmosphere. Here, flowing gas specifically means purging the gas.

[0052] Meanwhile, the nucleation rate and the nucleation growth rate must be similar for the average particle size (D 50A cathode active material precursor can be manufactured with a particle size of approximately 1 μm, uniform particle size, and high sphericity. However, in step (B), if nitrogen gas is flowed into the reactor at a flow rate of less than 20 volume% of the total volume of the reactor per minute, there is a problem that nucleation occurs more than nucleation of the cathode active material precursor particles, and if it is flowed at a flow rate of more than 50 volume%, there is a problem that nucleation occurs more than nucleation of the cathode active material precursor particles.

[0053] In steps (A) and (B) above, when the ammonium cation complex forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor is 0.1 to 0.4, an appropriate complex ion forming atmosphere is created in the reactor solution, which has the advantage of enabling the formation of a precursor with uniform particle size and excellent sphericity.

[0054] Meanwhile, if the above-mentioned ammonium cation complex-forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex-forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor is less than 0.1, the complex ion formation of transition metal ions is not properly performed, resulting in a problem where a precursor of about 1 μm is not produced, and the thickness of the primary particles is thin, making it difficult to realize a single-particle cathode active material. Furthermore, if the above-mentioned ammonium cation complex-forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex-forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor exceeds 0.4, nucleation growth cannot be suppressed, making particle size control impossible, and there is a problem of particles clumping together during the nucleation growth process, resulting in a failure to obtain good sphericity and span value.

[0056] According to the present invention, the transition metal-containing solution may contain 70 mol% or more of nickel, specifically 80 mol% or more, and more specifically 85 mol% or more, based on the total moles of transition metals.

[0057] The above transition metal-containing solution may include nickel raw material, cobalt raw material, and manganese raw material.

[0058] The above nickel raw material may be nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be Ni(OH)2, NiO, NiOOH, NiCO3ㆍ2Ni(OH)2ㆍ4H2O, NiC2O2ㆍ2H2O, Ni(NO3)2ㆍ6H2O, NiSO4, NiSO4ㆍ6H2O, Ni(SO3)2 or a combination thereof, but is not limited thereto.

[0059] The above cobalt raw material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be Co(OH)2, CoOOH, Co(OCOCH3)2ㆍ4H2O, Co(NO3)2ㆍ6H2O, CoSO4, Co(SO4)2ㆍ7H2O, Co(SO3)2 or a combination thereof, but is not limited thereto.

[0060] The above manganese-containing raw material may be a manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4, Mn(SO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, manganese fatty acid, manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0061] The above transition metal-containing solution may be prepared by adding nickel-containing raw materials, cobalt-containing raw materials, and manganese-containing raw materials to a solvent, specifically water, or a mixed solvent of an organic solvent that can be uniformly mixed with water (e.g., alcohol, etc.), but is not limited thereto. Meanwhile, if the above transition metal-containing solution further contains ions of one or more elements selected from Zr, Al, W, Ti, Nb, Ta, V, Mo, and B, the transition metal-containing solution may be prepared by adding raw materials containing one or more elements selected from Zr, Al, W, Ti, Nb, Ta, V, Mo, and B together to the solvent.

[0062] The above ammonium cation complex-forming agent may include, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or combinations thereof, but is not limited thereto. Meanwhile, the above ammonium cation complex-forming agent may be used in the form of an aqueous solution, in which case water or a mixture of water and an organic solvent (e.g., alcohol) that is uniformly miscible with water may be used as the solvent.

[0063] The above basic solution may include alkali compounds such as hydroxides of alkali metals or alkaline earth metals like NaOH, KOH, or Ca(OH)2, their hydrates, or combinations thereof, as precipitating agents. The above basic solution may also be used in the form of an aqueous solution, in which case water or a mixture of water and an organic solvent (e.g., alcohol) that is uniformly miscible with water may be used as the solvent.

[0065] Hereinafter, each step of the present invention will be described in detail.

[0067] Step (A) above is a step up to the point before the continuous stirred tank reactor (CSTR) is filled, in which a transition metal-containing solution, an ammonium cation complex forming agent, and a basic aqueous solution are continuously introduced into the reactor to generate and grow nuclei of cathode active material precursor particles through a precipitation reaction.

[0068] According to the present invention, step (A) may be performed under an inert atmosphere, specifically by flowing nitrogen gas into the reactor at a flow rate of 5 volume% or more and less than 20 volume% with respect to the total volume of the reactor per minute, specifically 7 volume% to 16 volume%, and more specifically 9 volume% to 12 volume%. In this case, the influence of air introduced from the outside during the reaction process can be blocked.

[0069] According to the present invention, step (A) may be performed under a pH of 12.0 to 13.0, specifically 12.3 to 12.9, and more specifically 12.4 to 12.8. In this case, the particle size of the positive electrode active material precursor can be made small and uniform.

[0070] According to the present invention, in step (A), the nucleation of the precursor particles may occur at a pH lower than the nucleation of the precursor particles. Specifically, in step (A), the nucleation of the precursor particles may occur at a pH about 0.1 lower than the nucleation of the precursor particles.

[0071] The co-precipitation reaction of step (A) above may be carried out at 40°C to 60°C, specifically 44°C to 56°C, and more specifically 48°C to 52°C. When the co-precipitation reaction of step (A) above is carried out at a temperature within the above range, the energy required for the co-precipitation reaction can be provided, thereby enabling a smooth co-precipitation reaction within the reactor.

[0072] The co-precipitation reaction of step (A) above may be carried out for 0.5 to 20 hours, specifically 2 to 14 hours, and more specifically 4 to 8 hours. When the co-precipitation reaction of step (A) above is carried out for a time within the above range, a positive active material precursor having appropriate particle size is produced while the reactor is simultaneously filled, so that a positive active material precursor having small and uniform particle size can be obtained in step (B).

[0074] Step (B) above is a step after the continuous stirred tank reactor (CSTR) is filled. When the reactor is filled, the overflow pipe is opened to obtain the positive active material precursor prepared in Step (A), and at the same time, nitrogen gas is flowed into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute, while continuously introducing a transition metal-containing solution, an ammonium cation complex forming agent, and a basic aqueous solution to generate and grow nuclei of positive active material precursor particles through a precipitation reaction.

[0075] In step (B) above, since the precipitation reaction continues while the overflow tube is open, the positive active material precursor can be obtained continuously.

[0076] According to the present invention, step (B) may be performed under a pH of 12.0 to 13.0, specifically a pH of 12.2 to 12.8, and more specifically a pH of 12.4 to 12.6. In this case, the particle size of the cathode active material precursor can be made small and uniform. With the overflow tube open, the average particle size (D 50 In order to continuously obtain a positive active material precursor that is small (approximately 1 μm), has a uniform particle size, and high sphericity, the above step (B) may occur at a lower pH than the above step (A).

[0077] According to the present invention, in step (B), the nucleation of the precursor particles may occur at a pH lower than the nucleation of the precursor particles. Specifically, in step (B), the nucleation of the precursor particles may occur at a pH about 0.1 lower than the nucleation of the precursor particles.

[0078] The co-precipitation reaction of step (B) above may be carried out at 40°C to 60°C, specifically 44°C to 56°C, and more specifically 48°C to 52°C. When the co-precipitation reaction of step (B) above is carried out at a temperature within the above range, the energy required for the co-precipitation reaction can be provided, thereby enabling a smooth co-precipitation reaction within the reactor.

[0079] The co-precipitation reaction of step (B) above has an average particle size (D 50 In order to obtain a precursor having a span of approximately 1 μm, a small span value, and high sphericity, the process may be carried out for 48 to 120 hours, specifically 72 to 106 hours, and more specifically 84 to 94 hours. When the co-precipitation reaction of step (B) is carried out for a time within the above range, it is possible to obtain a 1 μm cathode active material precursor having a narrow span and high sphericity, and consequently, it may help to manufacture a cathode active material in the form of a single particle.

[0081] positive electrode active material precursor

[0082] Next, a positive electrode active material precursor according to the present invention will be described.

[0084] The positive active material precursor according to the present invention has an average particle size (D 50 ) is 0.95㎛ to 1.5㎛, the span value according to Formula 1 below is 1.5 or less, and the sphericity is 1 to 1.3. The cathode active material precursor according to the present invention has an average particle size (D 50It has the advantage of having a high heat transfer rate during calcination for manufacturing positive electrode active materials, as it is small (approximately 1㎛), has a uniform particle size, and has high sphericity, and as a result, it can be used to manufacture single-particle positive electrode active materials.

[0085] [Equation 1]

[0086] Span = (D 95 -D5) / D 50

[0087] Meanwhile, average particle size (D 50 If the value is less than 0.95㎛, there is a problem that the particle size is too small and a spherical precursor is not formed, and if it is greater than 1.5㎛, there is a problem that a high-intensity grinding process is additionally required to make it into a single particle after calcination due to the relatively high density. Also, if the span value according to Equation 1 above exceeds 1.5, there is a problem that the thermal energy transferred to each particle is uneven, and if the sphericity exceeds 1.3, there is a problem that the thermal energy received from the outside by a single particle is not evenly distributed throughout the particle.

[0089] The above-mentioned positive active material precursor may be manufactured according to the method for manufacturing a positive active material precursor according to the present invention.

[0090] When manufacturing a cathode active material precursor using a continuous stirred tank reactor according to the previously disclosed method, although it is possible to form a precursor with small particle size, there was a problem in that it was difficult to manufacture a cathode active material precursor with uniform particle size and high sphericity because nucleation growth and nucleation occur simultaneously. However, when manufacturing a precursor according to the method for manufacturing a cathode active material precursor according to the present invention, the average particle size (D 50 There is an advantage in that the above-mentioned positive active material precursor is manufactured with a particle size of approximately 1㎛, uniform particle size, and high sphericity.

[0092] According to the present invention, the positive active material precursor may have a composition represented by the following chemical formula 1 or chemical formula 2.

[0093] [Chemical Formula 1]

[0094] Ni a1 Co b1 M1 c1 M2 d1 (OH)2

[0095] In the above chemical formula 1, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a1<1.0, 0 <b1<0.3, 0<c1<0.3, 0≤d1≤0.02이며,

[0096] [Chemical Formula 2]

[0097] Ni a2 Co b2 M1 c2 M2 d2 O·OH

[0098] In the above chemical formula 2, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a2<1.0, 0 <b2<0.3, 0<c2<0.3, 0≤d2≤0.02이다.

[0099] The above-mentioned positive active material precursor may contain 70 mol% or more of nickel (Ni), specifically 80 mol% or more, and more specifically 85 mol% or more, with respect to the total moles of metals excluding lithium.

[0101] According to the present invention, the cathode active material precursor may have a tap density of 1.3 g / ml or more and 1.5 g / ml or less, specifically 1.32 g / ml to 1.48 g / ml, and more specifically 1.34 g / ml to 1.47 g / ml. In this case, since the tap density is high relative to the average particle size, the packing ratio can be increased during calcination for manufacturing the cathode active material, thus providing the advantage of improving the productivity of the cathode active material.

[0103] positive electrode active material

[0104] Next, a positive active material, which is a calcined product of a mixture of a positive active material precursor and a lithium raw material according to the present invention, will be described.

[0106] The above positive active material can be manufactured by mixing the positive active material precursor of the present invention with a lithium raw material and then calcining it.

[0107] Examples of the above lithium raw materials include lithium-containing carbonates (e.g., lithium carbonate, etc.), hydrates (e.g., lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxides (e.g., lithium hydroxide, etc.), nitrates (e.g., lithium nitrate (LiNO3), etc.), chlorides (e.g., lithium chloride (LiCl), etc.), and one of these alone or a mixture of two or more of these may be used.

[0108] Meanwhile, the mixing of the above-mentioned positive active material precursor and the lithium raw material can be carried out as a solid-state mixing, and the mixing ratio of the above-mentioned positive active material precursor and the lithium raw material can be determined within a range that satisfies the atomic fraction of each component in the positive active material finally manufactured. For example, the above-mentioned positive active material precursor and the lithium raw material can be mixed in an amount such that the molar ratio of transition metal to Li is 1:0.9 to 1:1.2, specifically 1:0.98 to 1:1.1. When the above-mentioned precursor and the lithium raw material are mixed within the above range, a positive active material exhibiting excellent capacity characteristics can be manufactured.

[0109] The above firing may be performed at 600°C to 1000°C, specifically at 700°C to 900°C, and the firing time may be 5 hours to 30 hours, specifically at 8 hours to 15 hours, but is not limited thereto.

[0111] According to the present invention, the positive electrode active material may be manufactured from a positive electrode active material precursor according to the present invention and may be in the form of a single particle. This is because the average particle size (D) of the positive electrode active material precursor according to the present invention 50 This is because the particle size is small (approximately 1㎛), the particle size is uniform, and the sphericity is high, so the precursor can receive heat uniformly when mixed with lithium raw material and calcined.

[0113] The above positive active material may have a composition represented by the following chemical formula 3.

[0114] [Chemical Formula 3]

[0115] Li 1+x Ni a3 Co b3 M1 c3 M2 d3 O2

[0116] In the above chemical formula 3, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and -0.2≤x≤0.2, 0.7≤a3<1.0, 0 <b3<0.3, 0<c3<0.3, 0≤d3≤0.02이다.

[0117] The above positive active material may contain 70 mol% or more of nickel (Ni), specifically 80 mol% or more, and more specifically 85 mol% or more, with respect to the total moles of metals excluding lithium.

[0119] According to the present invention, the positive electrode active material may contain 0.8% by weight or less of residual lithium relative to the total weight of the positive electrode active material. Accordingly, a lithium secondary battery containing the positive electrode active material according to the present invention may have excellent performance.

[0121] anode

[0122] Next, a positive electrode comprising the positive electrode active material of the present invention described above will be explained.

[0124] The above-mentioned positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material according to the present invention.

[0125] As the positive active material has been described above, a detailed explanation is omitted, and only the remaining components are described in detail below.

[0127] The above positive current collector may include a highly conductive metal, and is not particularly limited as long as it facilitates the adhesion of the positive active material layer and is non-reactive within the voltage range of the battery. The above positive current collector may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. Additionally, the above positive current collector may typically have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive active material. It may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.

[0129] The above positive active material layer may, together with the positive active material, optionally include a conductive material and a binder as needed.

[0130] At this time, the positive active material may be included in an amount of 80 to 99 weight%, more specifically 85 to 98.5 weight%, based on the total weight of the positive active material layer. Excellent capacity characteristics can be exhibited when included within the above-mentioned content range.

[0131] The above conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powder or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used. The above conductive material may be included in an amount of 0.1 to 15 weight% based on the total weight of the positive electrode active material layer.

[0132] The above binder serves to improve the adhesion between positive active material particles and the adhesion between the positive active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogens thereof are substituted with Li, Na, or Ca, or various copolymers thereof, and one of these alone or a mixture of two or more may be used. The above binder may be included in an amount of 0.1 to 15 weight percent based on the total weight of the positive active material layer.

[0134] The above-described anode may be manufactured according to a conventional anode manufacturing method, except for using the above-described anode active material. Specifically, it may be manufactured by applying a composition for forming an anode active material layer, prepared by dissolving or dispersing the above-described anode active material and, optionally, a binder, a conductive material, and a dispersant in a solvent, onto an anode current collector, and then drying and rolling.

[0135] The above solvent may be a solvent generally used in the relevant technical field, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, or water, and one of these alone or a mixture of two or more may be used. The amount of the above solvent used is sufficient if it is sufficient to dissolve or disperse the anode active material, conductive material, binder, and dispersant, taking into account the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can exhibit excellent thickness uniformity when coated for anode manufacturing thereafter.

[0137] In addition, the anode may also be manufactured by casting the composition for forming the anode active material layer onto a separate support and then laminating the film obtained by peeling from the support onto an anode current collector.

[0139] electrochemical device

[0140] Next, an electrochemical device including the anode described above will be explained.

[0142] The above electrochemical device may specifically be a battery, a capacitor, etc., and more specifically, a lithium secondary battery.

[0143] Specifically, the above lithium secondary battery comprises a positive electrode, a negative electrode positioned opposite the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is identical to the one described above, a detailed description is omitted, and only the remaining components are described in detail below.

[0144] Additionally, the lithium secondary battery may optionally further include a battery container that accommodates the electrode assembly of the positive electrode, negative electrode, and separator, and a sealing member that seals the battery container.

[0146] In the above lithium secondary battery, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0147] The above-mentioned negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, the above-mentioned negative current collector may typically have a thickness of 3 μm to 500 μm, and, similar to the positive current collector, fine irregularities may be formed on the surface of the current collector to strengthen the bonding strength of the negative active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0149] The above-mentioned cathode active material layer optionally includes a binder and a conductive material together with the cathode active material.

[0150] As the above-mentioned negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium may be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; and SiO₂ βExamples include metal oxides capable of doping and dedoping lithium, such as (0<β<2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites comprising the metal compound and carbonaceous material, such as Si-C composites or Sn-C composites, and any one or more of these may be used. Additionally, a metallic lithium thin film may be used as the negative electrode active material. Furthermore, the carbon material may include low-crystallinity carbon and high-crystallinity carbon. Representative examples of low-crystallinity carbon include soft carbon and hard carbon, while representative examples of high-crystallinity carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes.

[0151] The above-mentioned negative electrode active material may be included in an amount of 80% to 99% by weight based on the total weight of the negative electrode active material layer.

[0152] The above binder is a component that assists in the bonding between the conductive material, the active material, and the current collector, and is typically added in an amount of 0.1% to 10% by weight based on the total weight of the negative active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0153] The above conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used.

[0155] The above-mentioned negative electrode active material layer may be manufactured by applying and drying a composition for forming a negative electrode active material layer, prepared by dissolving or dispersing a negative electrode active material and optionally a binder and a conductive material in a solvent, or by casting the composition for forming a negative electrode active material layer onto a separate support and then laminating the film obtained by peeling from the support onto a negative electrode current collector.

[0157] Meanwhile, in the above-mentioned lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a pathway for the movement of lithium ions. Any separator typically used in lithium secondary batteries may be used without special limitations, and it is particularly desirable that it has low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity. Specifically, a porous polymer film, such as a porous polymer film made from a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber, may be used. Furthermore, a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0159] In addition, the above electrolytes may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used when manufacturing lithium secondary batteries, but are not limited to these.

[0160] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0161] The above organic solvent may be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the above organic solvent may include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; and aromatic hydrocarbon-based solvents such as benzene and fluorobenzene. Carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms and may include a double bond, a directional ring, or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among these, a carbonate-based solvent is preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and a low-viscosity linear carbonate-based compound (e.g., ethylmethyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) is more preferred.In this case, using a mixture of cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9 can result in excellent performance of the electrolyte.

[0163] The above lithium salt may be used without special restrictions as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, as the anion of the above lithium salt, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - It may be at least one selected from the group consisting of, and the lithium salt is, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2) 2. LiCl, LiI, or LiB(C2O4)2, etc., may be used. It is preferable to use the lithium salt within the range of 0.1 to 2.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0165] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, the above additives may be included in an amount of 0.1 to 5 weight% based on the total weight of the electrolyte.

[0167] As described above, since the lithium secondary battery containing the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics, and lifespan characteristics, it is useful in portable devices such as mobile phones, laptop computers, and digital cameras, as well as in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0168] Accordingly, a battery module including the above-mentioned lithium secondary battery as a unit cell and a battery pack including the same may be provided.

[0169] The above battery module or battery pack can be used as a power source for one or more medium-to-large devices, including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0170] There are no specific restrictions on the external shape of the above lithium secondary battery, but it may be a cylindrical type using a can, a prismatic type, a pouch type, or a coin type.

[0171] The above lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but can also preferably be used as a unit cell in a medium-to-large battery module containing a plurality of battery cells.

[0172] Examples of the above-mentioned medium-to-large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, but are not limited to these.

[0174] The present invention will be explained in more detail below through specific embodiments.

[0176] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The embodiments of the present invention are provided to more completely explain the invention to those with average knowledge in the art.

[0178] Examples and Comparative Examples

[0179] Example 1

[0180] A transition metal aqueous solution with a concentration of 2.4 M was prepared by mixing NiSO4, CoSO4, and MnSO4 in deionized water in amounts such that the molar ratio of nickel:cobalt:manganese was 95.5:3.5:1.0.

[0181] The container containing the above transition metal aqueous solution, the container containing a 25 wt% concentration NaOH aqueous solution, and the container containing a 9 wt% concentration NH4OH aqueous solution were each connected to a continuous stirring tank reactor (10L).

[0182] Next, 2.6 L of deionized water was added to the reactor, and nitrogen gas was purged into the reactor at a rate of 1 L / min to remove dissolved oxygen from the water and create a non-oxidizing atmosphere inside the reactor. Subsequently, while continuing to purge nitrogen gas into the reactor at a rate of 1 L / min, 13.7 mL of a 25 wt% aqueous NaOH solution and 134.3 mL of a 9 wt% aqueous NH4OH solution were added, and the mixture was stirred at a stirring speed of 150 rpm at 50°C to adjust the pH inside the reactor to pH 12.5–13.0.

[0183] Subsequently, nitrogen gas was continuously purged into the reactor at a rate of 1 L / min and stirred at a stirring speed of 800 rpm, while the transition metal aqueous solution was continuously fed into the reactor at a rate of 0.58 L / hr, the NaOH aqueous solution at 0.35 L / hr, and the NH4OH aqueous solution at 0.06 L / hr, and the co-precipitation reaction was carried out for 6 hours at 50°C and pH 12.5~13.0 to generate and grow nuclei of cathode active material precursor particles.

[0184] Then, after about 6 hours, when the reactor was full, the overflow pipe was opened to obtain the cathode active material precursor, and at the same time, nitrogen gas was continuously purged into the reactor at a rate of 2 L / min (a flow rate of 20% of the total volume of the reactor per minute), and while stirring at a stirring speed of 800 rpm, the transition metal aqueous solution, NaOH aqueous solution, and NH4OH aqueous solution were continuously fed into the reactor at rates of 0.58 L / hr, 0.34 L / hr, and 0.06 L / hr, and the co-precipitation reaction was carried out for 94 hours at 50°C and pH 12.4~12.9, thereby generating and growing nuclei of cathode active material precursor particles, and continuously obtaining the cathode active material precursor.

[0185] The finally obtained cathode active material precursor is Ni 0.955 Co 0.035 Mn 0.01 It is a positive active material precursor having a (OH)2 composition.

[0186] For reference, during the co-precipitation reaction, the ammonium cation complex forming agent was added such that the molar ratio of ammonia contained in the ammonium cation complex forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor was 0.2.

[0188] Example 2

[0189] A cathode active material precursor was prepared in the same manner as in Example 1, except that when proceeding with the co-precipitation reaction, an aqueous NH4OH solution was continuously fed into the reactor at a rate of 0.08 L / hr instead of 0.06 L / hr.

[0190] For reference, during the co-precipitation reaction, the ammonium cation complex forming agent was added such that the molar ratio of ammonia contained in the ammonium cation complex forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor was 0.3.

[0192] Example 3

[0193] A cathode active material precursor was prepared in the same manner as in Example 1, except that when the reactor was full, the overflow tube was opened to obtain the cathode active material precursor, and nitrogen gas was continuously purged into the reactor at a rate of 4 L / min instead of 2 L / min (a flow rate of 40% of the total reactor volume per minute).

[0195] Comparative Example 1

[0196] A transition metal aqueous solution with a concentration of 2.4 M was prepared by mixing NiSO4, CoSO4, and MnSO4 in deionized water in amounts such that the molar ratio of nickel:cobalt:manganese was 95.5:3.5:1.0.

[0197] The container containing the above transition metal aqueous solution, the container containing a 25 wt% concentration NaOH aqueous solution, and the container containing a 9 wt% concentration NH4OH aqueous solution were each connected to a continuous filtration tank reactor (CFTR) (10L). For reference, the filter in the above CFTR reactor is located at 80 volume% of the total volume of the reactor.

[0198] Next, 2.6 L of deionized water was added to the reactor, and nitrogen gas was purged into the reactor at a rate of 1 L / min to remove dissolved oxygen from the water and create a non-oxidizing atmosphere inside the reactor. Subsequently, while continuing to purge nitrogen gas into the reactor at a rate of 1 L / min, 13.7 mL of a 25 wt% aqueous NaOH solution and 134.3 mL of a 9 wt% aqueous NH4OH solution were added, and the mixture was stirred at a stirring speed of 150 rpm at 50°C to adjust the pH inside the reactor to pH 12.5–13.0.

[0199] Subsequently, nitrogen gas was continuously purged into the reactor at a rate of 1 L / min and stirred at a stirring speed of 800 rpm, while the transition metal aqueous solution was continuously fed into the reactor at a rate of 0.58 L / hr, the NaOH aqueous solution at 0.35 L / hr, and the NH4OH aqueous solution at 0.06 L / hr, and the co-precipitation reaction was carried out for 4 hours at 50°C and pH 12.5~13.0 to generate and grow nuclei of cathode active material precursor particles.

[0200] Then, after about 4 hours, when the solution had risen to approximately 80% of the total volume of the reactor, the filter installed in the reactor was operated for 5 minutes to remove deionized water excluding the cathode active material precursor, thereby concentrating the cathode active material precursor (the transition metal aqueous solution, NaOH aqueous solution, and NH4OH aqueous solution were continuously being supplied, and the deionized water was removed only up to the location of the filter). After closing the filter, nitrogen was continuously purged into the reactor at a rate of 2 L / min (a flow rate of 20% of the total reactor volume per minute) and stirred at a stirring speed of 800 rpm, while continuously introducing the transition metal aqueous solution into the reactor at rates of 0.58 L / hr, 0.35 L / hr, and 0.06 L / hr, and carrying out a co-precipitation reaction at 50°C and pH 12.5~13.0. When the solution filled to about 90% of the total volume of the reactor, the process of removing deionized water by operating the filter again for 5 minutes was repeated, and the reaction was terminated after 10 hours so that the particle size did not exceed 1.5 μm.

[0201] The finally obtained cathode active material precursor is Ni 0.955 Co 0.035 Mn 0.01 It is a positive active material precursor having a (OH)2 composition.

[0203] Comparative Example 2

[0204] A cathode active material precursor was prepared in the same manner as in Example 1, except that when proceeding with the co-precipitation reaction, an aqueous NH4OH solution was continuously fed into the reactor at a rate of 0.01 L / hr instead of 0.06 L / hr.

[0205] For reference, during the co-precipitation reaction, the ammonium cation complex forming agent was added such that the molar ratio of ammonia contained in the ammonium cation complex forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor was 0.05.

[0207] Comparative Example 3

[0208] A cathode active material precursor was prepared in the same manner as in Example 1, except that when proceeding with the co-precipitation reaction, an aqueous NH4OH solution was continuously fed into the reactor at a rate of 0.12 L / hr instead of 0.06 L / hr.

[0209] For reference, during the co-precipitation reaction, the ammonium cation complex forming agent was added such that the molar ratio of ammonia contained in the ammonium cation complex forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor was 0.45.

[0211] Comparative Example 4

[0212] A cathode active material precursor was prepared in the same manner as in Example 1, except that when the reactor was full, the overflow pipe was opened to obtain the cathode active material precursor, and nitrogen gas was continuously purged into the reactor at a rate of 1 L / min instead of 2 L / min (a flow rate of 10 volume% relative to the total volume of the reactor per minute).

[0214] Comparative Example 5

[0215] A cathode active material precursor was prepared in the same manner as in Example 1, except that when the reactor was full, the overflow tube was opened to obtain the cathode active material precursor, and nitrogen gas was continuously purged into the reactor at a rate of 6 L / min instead of 2 L / min (a flow rate of 60% of the total reactor volume per minute).

[0217] Experimental Example

[0218] Experimental Example 1: Evaluation of Characteristics of Anode Active Material Precursor

[0219] The particle characteristics of the cathode active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5 above were evaluated.

[0221] 1) Evaluation of particle size and particle size distribution

[0222] The particle size of each cathode active material precursor prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was measured (based on a refractive index of 1.75) using a particle size distribution measuring device (S-3500, Microtrac), and the results are shown in Table 1 and Figure 1 below.

[0223] FIG. 1 is a graph showing the particle size distribution of the cathode active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5.

[0225] D5(㎛) D 50 (㎛) D 95 (㎛) Span((D 95 -D5) / D 50 ) value Example 1 0.76 1.06 1.61 0.80 Example 2 0.63 1.16 1.92 1.11 Example 3 0.58 1.18 2.17 1.35 Comparative Example 1 0.51 1.39 2.97 1.77 Comparative Example 2 0.53 1.52 3.47 1.93 Comparative Example 3 0.47 1.44 4.48 2.79 Comparative Example 4 0.47 1.34 12.40 8.90 Comparative Example 5 0.51 1.54 3.61 2.01

[0227] 2) Tap density evaluation

[0228] 50g of the positive active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were each filled into a 100mL container, and the apparent density of the particles obtained by vibrating under constant conditions was measured. Specifically, the tap density of the positive active material precursors was measured using a tap density tester (KYT-4000, Seishin). The measurement results are shown in Table 2 below.

[0229] Tap density (g / ml) Example 1 1.45 Example 2 1.47 Example 3 1.34 Comparative Example 1 1.28 Comparative Example 2 1.17 Comparative Example 3 1.74 Comparative Example 4 1.04 Comparative Example 5 1.53

[0231] 3) Evaluation of sphericity

[0232] The sphericity of the cathode active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was confirmed using a scanning electron microscope (SEM). Figures 2 to 9 are SEM images showing the cathode active material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 5, respectively. In each SEM image, the aspect ratio value, which is the ratio of the major axis length to the minor axis length in the cross-section of the cathode active material precursor particle, was obtained and represented as sphericity in Table 3 below.

[0233] Spherical shape Example 1 1.25 Example 2 1.25 Example 3 1.27 Comparative Example 1 1.36 Comparative Example 2 1.43 Comparative Example 3 1.46 Comparative Example 4 1.48 Comparative Example 5 1.34

[0235] Referring to Table 1, the cathode active material precursors of Examples 1 to 3 have an average particle size (D 50 It can be confirmed that the particle size is uniform with a span value of 1.5 or less and the average particle size of the positive active material precursors of Comparative Examples 1 to 5 is relatively large, and the span value also exceeds 1.5.

[0236] Referring to Table 3, it can be seen that in the case of Examples 1 to 3, the sphericity is 1.3 or less, whereas in the case of Comparative Examples 1 to 5, the sphericity exceeds 1.3. That is, it can be seen that the cathode active material precursors prepared in the examples are particles close to spherical, whereas the cathode active material precursors prepared in the comparative examples are not.

[0237] Referring to Table 2, it can be seen that the cathode active material precursors of Examples 1 to 3 have a higher tap density than the cathode active material precursors of Comparative Example 1 (using a CFTR reactor, which is a type of batch reactor), Comparative Examples 2 and 4. From this, it can be seen that a relatively larger amount of cathode active material precursor can be loaded into a single tray during calcination for the manufacture of cathode active materials, resulting in excellent productivity. On the other hand, although the cathode active material precursors of Comparative Examples 3 and 5 have a high tap density, they are not uniform and do not have good sphericity (see Tables 1 and 3 and SEM images), so they cannot be considered high-quality precursors.

[0239] Experimental Example 2: Evaluation of Sintering Uniformity

[0240] The cathode active material precursors of Example 1 and Comparative Example 1 were each mixed with LiOH in a molar ratio of 1:1.05, and then calcined at 830–880°C for 3–7 hours under an oxygen atmosphere, followed by calcination at 750–800°C for 8–12 hours to prepare the cathode active material. The morphology of the cathode active material prepared using the respective cathode active material precursors of Example 1 and Comparative Example 1 was confirmed using a scanning electron microscope (SEM). Figure 10 is an SEM image of the cathode active material prepared using the cathode active material precursor of Example 1, and Figure 11 is an SEM image of the cathode active material prepared using the cathode active material precursor of Comparative Example 1.

[0242] Referring to FIGS. 10 and 11, it can be seen that the positive active material prepared using the positive active material precursor of Example 1 is in the form of single particles, whereas the positive active material prepared using the positive active material precursor of Comparative Example 1 does not form a single particle shape well. This is because the positive active material precursor of Example 1 has an average particle size (D 50 This is because the positive electrode active material precursor of Comparative Example 1 is small at the 1㎛ level, has a span value of 1.5 or less, and a sphericity of 1.3 or less.

[0244] Experimental Example 3: Evaluation of Residual Lithium

[0245] After preparing a positive electrode active material using the positive electrode active material precursors of Example 1 and Comparative Example 1 in the same manner as in Experimental Example 2, the amount of residual lithium present in each positive electrode active material was measured. Specifically, 5g of each positive electrode active material was added to 100ml of deionized water, stirred for 5 minutes, and then filtered. 0.1M HCl was added to the filtered solution to perform titration (Metrohm 888pH Titrande). Two inflection points were observed after titration; the amount of 0.1M HCl added at the point where the inflection point occurred (the amount of 0.1M HCl used until the pH reached 4) was determined to calculate the amount of residual lithium. The results are shown in Table 4 below. In Table 4 below, the content of Li2CO3 and LiOH is expressed as weight% relative to the total weight of the positive electrode active material.

[0246] Li2CO3 (wt%) LiOH (wt%) Total (Weight%) Example 1 0.357 0.378 0.735 Comparative Example 1 0.506 0.391 0.897

[0248] Referring to Table 4, the positive active material prepared using the positive active material precursor of Example 1 has a lower residual lithium content compared to the positive active material prepared using the positive active material precursor of Comparative Example 1, so the lithium secondary battery containing the positive active material according to the present invention can have excellent performance.

[0250] Consequently, the positive electrode active material precursor produced by the manufacturing method of the present invention has an average particle size (D 50 It can be seen that the particle size is small (approximately 1 μm), the particle size is uniform, and the sphericity is high, and accordingly, a single-particle cathode active material can be easily manufactured. In addition, since the method for manufacturing the cathode active material precursor of the present invention utilizes a CSTR reactor, it can be seen that there is no limit to the production volume.

Claims

Claim 1 (A) A step of continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution into a continuous stirred tank reactor (CSTR) to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; and (B) when the reactor is full, open the overflow pipe to obtain the positive active material precursor prepared in step (A), and simultaneously flow nitrogen gas into the reactor at a flow rate of 20% to 50% of the total volume of the reactor per minute, while continuously introducing a transition metal-containing solution, an ammonium cation complex-forming agent, and a basic aqueous solution to generate and grow nuclei of positive active material precursor particles through a precipitation reaction; wherein in steps (A) and (B), the ammonium cation complex-forming agent is introduced such that the molar ratio of ammonia contained in the ammonium cation complex-forming agent to the total molar amount of transition metal contained in the transition metal-containing solution introduced into the reactor is 0.1 to 0.

4. Claim 2 A method for manufacturing an anode active material precursor according to claim 1, wherein the transition metal-containing solution contains 70 mol% or more of nickel with respect to the total moles of transition metals. Claim 3 A method for manufacturing a positive electrode active material precursor according to claim 1, wherein step (A) is performed under an inert atmosphere. Claim 4 A method for manufacturing a positive electrode active material precursor according to claim 1, wherein step (A) is performed by flowing nitrogen gas into the reactor at a flow rate of 5% or more and less than 20% of the total volume of the reactor per minute. Claim 5 A method for manufacturing a positive electrode active material precursor according to claim 1, wherein steps (A) and (B) are performed under a pH of 12.0 to 13.

0. Claim 6 A method for manufacturing a cathode active material precursor according to claim 1, wherein the nucleation growth of precursor particles in steps (A) and (B) occurs at a pH lower than the nucleation of precursor particles. Claim 7 Average particle size (D 50 A positive electrode active material precursor having a thickness of 0.95㎛ to 1.5㎛, a span value according to the following Equation 1 of 1.5 or less, and a sphericity of 1 to 1.3: [Equation 1] Span = (D 95 -D5) / D 50 . Claim 8 The positive active material precursor of claim 7, wherein the positive active material precursor has a composition represented by the following chemical formula 1 or chemical formula 2: [Chemical Formula 1]Ni a1 Co b1 M1 c1 M2 d1 (OH)2 In the above chemical formula 1, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a1<1.0, 0 <b1<0.3, 0<c1<0.3, 0≤d1≤0.02이며,[화학식 2]Ni a2 Co b2 M1 c2 M2 d2 O·OH In the above chemical formula 2, M1 is one or more selected from Mn and Al, and M2 is one or more selected from W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.7≤a2<1.0, 0 <b2<0.3, 0<c2<0.3, 0≤d2≤0.02이다. Claim 9 In claim 7, the positive active material precursor is a positive active material precursor having a tap density of 1.3 g / ml or more and 1.5 g / ml or less. Claim 10 A positive active material that is a calcined product of a mixture of a positive active material precursor and a lithium raw material according to claim 7. Claim 11 In claim 10, the positive active material is a positive active material in the form of a single particle.

Citation Information

Patent Citations

  • Information processing device, method for control of information processing device, and program for control of information processing device

    JP2018147068A

  • Continuous mass-production apparatus for precursor of secondary battery by co-precipitation method

    KR1020140107749A

  • Nickel-based active material precursor for lithium secondary battery, preparing method thereof, nickel-based active material for lithium secondary battery formed thereof, and lithium secondary battery comprising positive electrode including the nickel-based active material

    KR1020200019571A

  • Reactor, methods for preparing precursors of cathode active materials for lithium ion secondary batteries by using the same, precursors prepared by the same, cathode active materials

    KR1020160083617A

  • Nickel-based active material precursor for lithium secondary battery, preparing method thereof, nickel-based active material for lithium secondary battery formed thereof, and lithium secondary battery comprising positive electrode including the nickel-based active material

    KR1020200001082A